Relationship Of Mother's Knowledge Level With Basic Immunization Completeness In Children At Posyandu Bungatanjung Ciamis - Suhanda Suhanda; Yuyun Rahayu; Elisa Permatasari; Iif Taufiq El Haque; Asep Gunawan (LPPM STIKes Muhammadiyah Ciamis, 2020)
Immunization is a program that is much needed in the prevention of various infectious diseases and avoiding disabilities and child mortality. One of the efforts carried out by the government is by providing counseling to mothers to bring their children to get immunizations, especially carrying out 5 Complete Basic Immunizations, namely Hepatitis B, BCG, Polio, DPT, Measles and also striving to ensure access to services in areas reached by work the same as across other sectors. This is to determine the relationship between the mother's level of knowledge and the completeness of basic immunization for children at the Bungatanjung Posyandu, Cigembor Village, the working area of the Ciamis Health Center. The research method in this study is to use quantitative research methods with a cross-sectional research design, a population of 47 mothers, and sampling using a total sampling method. The results of the study showed that there were 30 people (78.9%) in good category knowledge, 8 people in poor category knowledge (21.1%), 33 people (86.8%) who completed basic immunization in the complete category, and 5 incomplete categories. (13.2%) with a statistical p-value of 0.022. The conclusion of this study is that there is a significant relationship between the level of maternal knowledge and the completeness of basic immunizations for children at the Bungatanjung Posyandu, Cigembor Village, the working area of the Ciamis Health Center.